Digoxin and association with mortality in patients discharged from hospital with atrial fibrillation, with or without heart failure. (24th May 2021) - Mpotis, M; Kartas, A; Samaras, A; Akrivos, E; Vrana, E; Liampas, E; Papazoglou, A; Moysidis, D; Papanastasiou, A; Baroutidou, A; Karvounis, H; Tzikas, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: MISOAC- AF study group BACKGROUND: Digoxin is widely used in atrial fibrillation (AF) and heart failure (AF). However, established evidence is conflicting regarding its association with clinical outcomes. AIM To investigate the relation between digoxin and adverse outcomes in patients with AF, with or without HF, in a contemporary AF cohort. METHODS: We performed a retrospective analysis of data from 698 patients, originating from the MISOAC- AF (Motivational Interviewing to Support Oral AntiCoagulation Adherence in patients with non-valvular Atrial Fibrillation) trial, and followed over a median of 2.5 years. HF was denoted at baseline. The primary outcome was all-cause mortality and the secondary outcome was all-cause hospitalization, in a time-to-event analysis. Propensity scores were used to derive matched populations, balanced on key baseline covariates. To limit potential confounding, we also implemented inverse probability of treatment weighting (IPTW) analysis. RESULTS: Among patients with HF, 10.5% (n = 39) were administered digoxin at baseline, whereas 89.5% (n = 331) were not. Digoxin administration was not associated with an increased risk of death (hazard ratio (HR) in the digoxin group, 1.21; 95% Confidence Interval (CI), 0.69 to 2.13, p = 0.5) or hospitalization of any cause (HR 1.15; 95% CI, 0.67 to 1.96; p = 0.6). Among patients without HF, 3.5% (n = 11) were administered digoxin, with neutral effects on all-cause mortality (HR: 3.25; 95% CI, 0.98 to 10.70), p = 0.06) and all-cause hospitalization (HR, 1.15; 95% CI, 0.67 to 1.96, p = 0.60). Consistent qualitatively results were observed using IPTW. CONCLUSIONS: Among patients with AF, digoxin administration was not associated with an increased risk of death and hospitalization of any cause, irrespective of HF status.